Secret selves : confession and same-sex desire in Victorian autobiography - Buckton, Oliver S. (University of North Carolina Press, 1998)
Focusing on the representation of same-sex desire in Victorian autobiographical writing, Oliver Buckton offers significant new readings of works by such influential 19th-century writers as Edward Carpenter, John Henry Newman, John Addington Symonds, and, in an epilogue, E.M. Forster, and reveals the "confessional" elements of their writings.